PERANAN PONDOK PESANTREN AZZUBIR DALAM PEMBINAAN AKHLAQ MASYARAKAT DESA TALESAH KECAMATAN TLANAKAN KABUPATEN PAMEKASAN - Munib, Abdul (Universitas Islam Madura, 2017)
The Boarding school is one of the institution that is the result of education itself will go into the community to practice it. Obviously, people have expected the graduations of the boarding school are also able to answer the challenges today. When viewed qualitatively, boarding school has important figures to the globalization and building development. Besides that, the boarding school as an institution and as a religious proselytizing villages need the support from the society surrounding it, during the relationship between school and the society is built by a religious motivation, so that society become the main supporting of religious school both socially and politically. So that the boarding school has a strong influence on the surrounding society as guidance them, the boarding school is the biggest powerful to be great value in the formation of public morality and behavior.